Perbedaan Persepsi Akuntan Publik dan Non-Publik Terhadap Kode Etik Akuntan Indonesia - Adi Mintoro; Sonny Hersona (At-Tadbir : jurnal ilmiah manajemen, 2021)
This study examines the differences in perceptions of public accountants and non-public accountants to the code of ethics of Indonesian accountants, in order to determine whether there are differences in perceptions between public accountants and non-public accountants to the code of ethics of Indonesian accountants. The sample used is 110 samples consisting of 55 respondents, 55 respondents, public accountants and non-public accountants in Jakarta. Methods of data analysis using statistical tests and paired difference test t test at the level of 0.05. The analysis and hypothesis testing that have been carried out show that there are differences in positive perceptions between Public Accountants and the Code of Ethics for Non-Public Accountants. The Indonesian Institute of Accountants, seen from the t-test results, can be stated that public and non-public accountants have a good appreciation and interpretation of the Code. Indonesian Accountant. In addition, from the results of hypothesis testing, there is no difference in perception between Public Accountants and Non-Public Accountants.Keywords: Difference Perceptions, Public Accountant, Non Public Accountants, Indonesia Accounting  Code of Conduct.